ИНСТИТУЦИОНАЛЬНАЯ СРЕДА РАЗВИТИЯ НАУКОЕМКОГО СЕКТОРА И ИННОВАЦИОННОГО ПРЕДПРИНИМАТЕЛЬСТВА В СТРАНАХ ЕВРАЗИЙСКОГО ЭКОНОМИЧЕСКОГО СОЮЗА (Экономика: стратегия и практика, 2019)
This article provides a comparative analysis of the current state and development of the institutional environment of high-tech science-intensive sector of the Eurasian economic Union as a key factor in the development of innovative entrepreneurship. Comparison of the level of development of knowledge-based GDP of the member States of the Eurasian economic Union indicates a relatively low level of these indicators. The stable low level of knowledge intensity of the countries of the Eurasian economic Union causes a relatively low level of innovative development of the economy and a high level of technological dependence of economic agents. Therefore, the creation and development of an institutional environment of high-tech science-intensive sector that meets international requirements is a key factor in overcoming the backlog in the innovative development of the countries of the Eurasian economic Union. The methodology of the institutional environment analysis is as follows, the initial period of creation of the regulatory framework of scientific and innovative activity, formation of the main subjects of innovative infrastructure, development of conceptual and program-target bases of strategic planning of innovative policy for the countries of the Eurasian economic Union is defined. It is established that despite the more than 20-year period of formation and development of the national innovation system of the Eurasian economic Union, the main problems of ensuring the effective work of the service organization and the proper resource support for innovation are still not solved. According to the results of the comparative analysis, it is established that at the moment only Russia has a sufficiently developed institutional environment of the knowledge-intensive sector, all other countries are experiencing financial constraints and must integrate their national innovation policies within the framework of the Eurasian economic Union. The results of this study can be used in the direction of adjusting national policies for the development of high-tech innovative entrepreneurship, taking into account the application of effective practices of institutional support of national innovation systems.